Transient comparison of techniques to counter multi-drug resistant bacteria: prime modules in curation of bacterial infections - Naveed, Muhammad; Waseem, Muhammad; Mahkdoom, Izma; Ali, Nouman; Asif, Farrukh; Hassan, Jawad ul; Jamil, Hamza (Frontiers in Antibiotics, 2024)
Multidrug-resistant organisms are bacteria that are no longer controlled or killed by specific drugs. One of two methods causes bacteria multidrug resistance (MDR); first, these bacteria may disguise multiple cell genes coding for drug resistance to a single treatment on resistance (R) plasmids. Second, increased expression of genes coding for multidrug efflux pumps, which extrude many drugs, can cause MDR. Antibiotic resistance is a big issue since some bacteria may withstand almost all antibiotics. These bacteria can cause serious sickness, making them a public health threat. Methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), Multidrug resistant Mycobacterium tuberculosis (TB), and CRE are gut bacteria that resist antibiotics. Antimicrobial resistance is rising worldwide, increasing clinical and community morbidity and mortality. Superbugs have made antibiotic resistance in some environmental niches even harder to control. This study introduces new medicinal plants, gene-editing methods, nanomaterials, and bacterial vaccines that will fight MDR bacteria in the future.